EFISIENSI USAHA PENANGKAPAN IKAN DENGAN KAPAL MOTOR DI PELABUHAN PERIKANAN PANTAI SADENG KABUPATEN GUNUNGKIDUL - Pandhu Rochman Suosa; Any Suryantini; Lestari rahayu Waluyati (Agro Ekonomi, 2014)
This research aims to determine (a) the factors that affect the productivity of the fish effort, (b) the level of technical price/allocative, economic eficency and revenue of fishing effort in fishing port Sadeng, Gunungkidul. The research was conducted using a survey. Determination of the study area is purposively. Respondent is selected by simple random sampling. Respondent is the owner of the motor vessel boat using gillnet and handline fishing gear, as many as 32 people.Data analysis is amultiple linear regression, calculating the level of efficiency and revenue. The results showed that factor significantly affect the productivity of fishing effort is the amount of fuel, fishing gear mesh size and number of crew (ABK). Value of technical efficiency of fishing effort (ET) is 0,99 while price efficiency (EH) is 5,117 and value of economic efficiency (EE) is 5,065. Revenues of fishing effort is Rp 5.854.072/trip and the value of R/C is 1,47/trip means fishing in Sadeng is profitable and feasible to be developed.